2023
DOI: 10.3390/ijms24021636
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Perturbation and Host Response Induce Redox Pathway Upregulation along the Gut–Liver Axis during Giardiasis in C57BL/6J Mouse Model

Abstract: Apicomplexan infections, such as giardiasis and cryptosporidiosis, negatively impact a considerable proportion of human and commercial livestock populations. Despite this, the molecular mechanisms of disease, particularly the effect on the body beyond the gastrointestinal tract, are still poorly understood. To highlight host–parasite–microbiome biochemical interactions, we utilised integrated metabolomics-16S rRNA genomics and metabolomics–proteomics approaches in a C57BL/6J mouse model of giardiasis and compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The interaction also decreased the expression of cysB genes, responsible for producing H 2 S [ 26 ], which is known to be an anti-inflammatory and cryoprotective metabolite in the intestine [ 27 ]. We have also noted that during Giardiasis infection in mice, the populations of Autopobiaceae and Desulfovibrionaceae increased, while that of Akkermansiaceae decreased [ 28 ], in the gut.…”
Section: Life Cycle and Infection Mechanismmentioning
confidence: 99%
See 4 more Smart Citations
“…The interaction also decreased the expression of cysB genes, responsible for producing H 2 S [ 26 ], which is known to be an anti-inflammatory and cryoprotective metabolite in the intestine [ 27 ]. We have also noted that during Giardiasis infection in mice, the populations of Autopobiaceae and Desulfovibrionaceae increased, while that of Akkermansiaceae decreased [ 28 ], in the gut.…”
Section: Life Cycle and Infection Mechanismmentioning
confidence: 99%
“…The observations from Giardia -infected children showed vitamin A malabsorption, not only from intestinal parasitism, but also indirectly via liver-based retinol mobilization. Our study [ 28 ] showed that depletion of Akkermansiaceae spp. in the gut caused oxidative stress across the gut–liver axis, leading to elevated glutathione metabolism, especially in the small intestine, serum, and liver.…”
Section: Cross-organ Impactsmentioning
confidence: 99%
See 3 more Smart Citations